Research Movements and Theorizing Dynamics in Management and Organization Studies - Clegg, Stewart; Pina e Cunha, Miguel; Berti, Marco (Academy of Management Review, 2022)
In this article we propose a conceptual model of the processes that regulate theory selection and retention in Management and Organization Studies. Considering the many sources of theoretical variety that characterize our field, what requires explanation is both the proliferation of theories as well as the decline of some schools of thought. We argue that research programs (ordered sequences of theories) lose momentum when the research movements that develop and maintain them fail to attend to some organizing priorities. By conceptualizing theorizing as form of organizing, we describe how research movements dynamically arrange sociomaterial elements (grammars, thought styles, material artefacts and empirical craft), arguing that their sustainability depends on their capacity effectively to navigate the paradoxical tensions that derive from these organizing efforts.